SOLUTION DRAFT TO ENGLISH SKILL PROBLEMS OF INDONESIAN EDUCATIONAL INSTITUTIONS - Zainuddin, Zainuddin; Delavari, Hilda (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2024)
English is a global language that dominates various aspects of life, including science, information technology, education, politics, economics, and culture. However, many students in Indonesia, from elementary school to college, struggle with English proficiency despite years of study. This issue stems from a lack of practical application in learning English, where the language is often treated as a theoretical subject rather than a practical skill. This study aims to identify solutions to these challenges in English language learning through a literature review of relevant sources, including e-journals, e-books, articles, and academic journals. The findings suggest that effective English learning should emphasize practice and active engagement, particularly through trial and error, to help students build confidence and improve their skills. Key solutions include encouraging students to practice speaking, listening, reading, and writing regularly, and integrating English into daily activities, such as listening to English songs or reading English books. Confidence-building is identified as crucial for improving English language skills.